GENETIC EFFECT AND PREVALENCE OF CLASS III MALOCCLUSION IN DIFFERENT POPULATION: AN OVERVIEW - SHIFAT A NOWRIN,; MOHAMMAD KHURSHEED ALAM,; REHANA BASRI, (International Journal of Pharma and Bio Sciences, 2015)
The prime aim of this review is to highlight the genetic effect and prevalence of class III malocclusion in different population. A literature search was conducted. Evidence from previous studies also established that class III malocclusion is strongly influenced by the genetic factors. May be class III malocclusion had developed by polygenic or monogenic mode of inheritance. But the environmental factors also responsible for this trait. Class III malocclusion has been the topic of intension and eager to many researchers. Researchers concluded that diverse combinations of skeletal and dental rudiments are drawn in to produce class III malocclusion. Genome wide linkage scan technology can detect several chromosomal regions, responsible for the mandibular prognathism. However, very few genome wide family based linkage study have been done for the determination of the mandibular prognathism. This article motivated on understanding the genetic influence and the prevalence of class III malocclusion in different population.